PENGARUH UKURAN PERUSAHAAN KLIEN, PERGANTIAN MANAJEMEN, KEPEMILIKAN INSTITUSIONAL, RENTABILITAS DAN KOMPLEKSITAS PERUSAHAAN TERHADAP AUDITOR SWITCHING (Studi Empiris pada Perusahaan LQ-45 yang Terdaftar di Bursa Efek Indonesia (BEI) tahun 2011-2016) - Widy Ayu Ocktaviany; Hardi Hardi; Rheny Afriana Hanif (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2018)
This study aims to examine the effect of client’s size, change in management, institutional ownership, rentability and company’s complexity on auditor switching. This quantitave research used secondary data of companies listed in Indonesia Stock Exchange in 2011-2016. The analytical technique that is used to perform the hypothesis testing in purposive sampling with some criterias, therefore, the number of samples obtained were 117 samples from 19 companies. The data was analyzed using logistic regression method by SPSS (Statistical Product and Service Solution) version 25. The result of this study indicated that client’s size, change in management, and company’s complexity influence the auditor switching in the companies, while the institutional ownership and rentability don’t influence the auditor switching in the companies. The amount of coefficient determination (r2 ) of the influence of client’s size, change in management, institutional ownership, rentability, and company’s complexity on auditor switching was 68,8% meanwhile, the 31,2% left is probably influenced by the other variables which are not included in this study.Keywords: auditor switching, client’s size, change in management, institutional ownership, rentability, company’s complexity